Analisis Desain Gagang Cangkul Berdasarkan Antropometri Petani Pria dan Beban Kerja Penggunanya pada Lahan Sawah Di Kecamatan Wedung, Demak, Jawa Tengah - Tri Novita Sari; Raizummi Fil’aini; Dwi Cahyani (Teknik Industri Universitas Indraprasta PGRI, 2020)
Hoe is a manual shoveling tool to cultivate on narrow land. Shoveling in Demak is still done manually using human labor, so causing fatigue and even injury. Conformity between the machine/tools in this case the hoe with its users is needed in order to create an effective, comfortable, safe, healthy and efficient work atmosphere. The anthropometric data is needed to create this conformity. This study aims to analyze suitable hoe handle based on anthropometric data of male farmer in Wedung district, Demak, Central Java to find out farmer workload (qualitative and quantitative workload and energy cost (kcal/min.kg, kcal/ha.kg dan kcal/quintal.kg) from each farmer who used the hoe. The four male farmers using heart rate parameter were observed to find out energy cost and workload. Based on anthropometric data, the recommended hoe handle design that suitable for farmers in Wedung district, Demak, Central Java are 79 cm for length, 2.08 cm for diameter of center hoe handle grip, 2.48 for diameter of bottom grip and 9.94 cm for length of top to center hoe handle grip. The qualitative workload, the hoe-shoveling activity is categorized as “heavy work” which is in average consuming 10322.5 kcal/ha energy cost per hectare, and 11.11 kcal/quintal energy cost per quintal shoveling work of soil.